Favorable 10-year outcomes of osteochondral autologous transplantation for spontaneous osteonecrosis of the knee following subchondral insufficiency fracture with optimal alignment correction - Kohei Nishitani; Yasuaki Nakagawa; Masahiko Kobayashi; Shinichiro Nakamura; Shogo Mukai; Shinichi Kuriyama; Shuichi Matsuda (Knee Surgery & Related Research)
Abstract Purpose The long-term effect of osteochondral autologous transplantation (OAT) on spontaneous osteonecrosis of the knee (SONK) following subchondral insufficiency fracture remains unclear. This study aimed to evaluate the long-term survivorship and clinical outcomes of OAT for SONK, with a focus on factors associated with clinical success. Methods Patients who underwent OAT for SONK between 1998 and 2009 were retrospectively reviewed. Survivorship was assessed using Kaplan–Meier analysis, with revision surgery as the endpoint. Clinical outcomes were evaluated using the International Knee Documentation Committee (IKDC) subjective score obtained preoperatively and at final follow-up. Clinical failure was defined as an IKDC score below the patient acceptable symptom state (PASS; 62.1 points). The association between final IKDC score and postoperative femorotibial angle (FTA) was analyzed using linear and quadratic regression. Results A total of 33 OATs were included (mean age: 64.6 ± 8.0 years; mean lesion size: 3.9 ± 1.7 cm2). High tibial osteotomy was performed in 15 patients with FTA > 180°, and 24 patients were followed for ≥ 10 years (mean: 13.7 ± 3.4 years). One arthroplasty was performed at 14.2 years, yielding a 15-year survival rate of 88%. The IKDC score improved significantly (35.0 ± 12.6 to 70.6 ± 14.1, p < 0.001), with a clinical success rate of 79.2%. Quadratic regression showed optimal postoperative FTA between 163.1° and 178.3° for achieving PASS. Conclusions OAT may provide favorable long-term survivorship and clinical outcomes in SONK, particularly when postoperative alignment is appropriately corrected.